Breeding for the improvement of indigenous chickens of Bangladesh: evaluation of performance of first generation of indigenous chicken - Faruque, Shakila; Bhuiyan, AKFH; Ali, Md Yousuf; Joy, Ziaul Faruque (Asian Journal of Medical and Biological Research, 2017)
Pure breeding is necessary for the conservation and improvement of indigenous chicken genetic resources. Present research is a part of the long-term selection program being undertaken to evaluate the performance and expected response to selection of first generation (G1) of three indigenous chicken genotypes under intensive management in Bangladesh. A total of 1439-day-old chicks comprising of 3 genotypes namely Naked Neck (NN), Hilly (H) and Non-descript Desi (ND) were hatched for this study. In first generation (G1), selection was practiced on body weight at 8 and 16 weeks of age, on the basis of their breeding value. At 40-week of age, selection will be practiced on the basis of an index comprising the parameters of age at first egg (ASM), body weight (BW), egg production (EP) and egg weight (EW). At 8, 10 and 12 weeks of age, six birds from each genotype were slaughtered to analyze the meat yield traits. Data were analyzed in CRD by General Linear Model Univariate Procedure. Significantly (P<0.001) highest body weight of day-old chicks (28.65±0.12 g) and daily weight gain in all stages were found in H genotype than other two genotypes. Although there was significant (P<0.001) difference in live weight between ages at slaughter, dressing percent (65.87 - 66.89 %) of different ages was similar (P>0.05) but was affected (P<0.001) by genotype. Body weight at 8 weeks of age was expected to improve by 58.98 vs. 11.50; 81.56 vs. 40.91 and 53.81 vs. 15.82 g; respectively for ND, H and NN males and females. In terms of body weight and growth traits H genotype was superior and NN genotype was for dressing percentage. As a result of selection; chick weight, body weight at all stages increased and ASM reduced in first generation than foundation stock. These findings give an impetus for continuing the pure breeding research for more generations. Asian J. Med. Biol. Res. March 2017, 3(1): 72-79